Review Effect of Aloe vera on Wound Healing: Review: Effect of Aloe vera on Wound Healing (Biological Sciences - PJSIR, 2020)
Skin acts as a protective barrier of body. It keeps the internal body organs safe from external environmental conditions which can prove harmful for them. So, maintenance of skin integrity is very important for normal functioning of body. In our daily life body of both animals and humans encounter to different types of violence, some of them are of such a severity that they break the skin continuity. This breakage of skin continuity is termed as wound. Whenever, the skin continuity is broken, internal organs of body are exposed. This is a dangerous situation and can be fatal for life. Immediate response of skin after wound is the start of wound healing process which starts automatically. This process can be assisted in a number of ways by keeping the wound free from bacterial contamination, moisture and dirt. For this purpose a variety of antiseptic dressings are available which when applied topically support wound healing process. They prevent wound to be contaminated by any micro-organism and reduce wound healing time. Aloe vera is one of them, it possess significant wound healing properties. Herbs have been integral to both traditional and non-traditional forms of medicine dating back at least 5000 years. Herbal medicines, especially in wound management involve disinfection, debridement and provision of a suitable environment for aiding the natural course of healing. The super focus of this review is to summarize the findings of earlier scientists with authentic concluding verse for utilization of herbal medicines (Aloe vera) being safe, readily available and cheaper.